Obesity under affluence varies by welfare regimes: The effect of fast food, insecurity and inequality - Offer, A; Pechey, R; Ulijaszek, S (Elsevier, 2010)
Among affluent countries, those with market-liberal welfare regimes (which are also English-speaking) tend to have the highest prevalence of obesity. The impact of cheap, accessible high-energy food is often invoked in explanation. An alternative approach is that overeating is a response to stress, and that competition, uncertainty, and inequality make market-liberal societies more stressful. This ecological regression meta-study pools 96 body-weight surveys from 11 countries c. 1994–2004. The fast-food ‘shock’ impact is found to work most strongly in market-liberal countries. Economic insecurity, measured in several different ways, was almost twice as powerful, while the impact of inequality was weak, and went in the opposite direction.